Sistem Pakar Deteksi Potensi Obesitas Dilingkungan Universitas Islam Negeri Sumatera Utara Menggunakan NaiVe Bayes Clasifier - Putra, Hardiansyah; Harahap, Inun Suryani (Jurnal Media Teknik Elektro dan Komputer, 2024)
This study aims to classify the potential for obesity among students in the environment of UIN SU Medan using the Naïve Bayes Classification method. The prevalence of obesity has become a serious problem in various countries, with significant contributions from critical periods such as prenatal, infancy, adiposity rebound, and adolescence. The use of technology has become widespread in various layers of society, making knowledge and preventive efforts crucial in addressing obesity. Lifestyle changes due to increased time-consuming activities can affect the health of the academic community. Therefore, the application of technology is essential in addressing obesity from adolescence to adulthood. The Naïve Bayes Classification method has been found to be suitable for classifying the likelihood of obesity among the academic community in the UIN SU Medan environment. However, it is important to optimize the training and testing classification process by storing the results in memory (database) to enhance the classification process.